Percutaneous lung microwave ablation versus lung resection in high-risk patients. A monocentric experience - Mendogni, Paolo; Daffrè, Elisa; Rosso, Lorenzo; Palleschi, Alessandro; Righi, Ilaria; Carrinola, Rosaria; Damarco, Francesco; Polli, Federico; Ierardi, Annamaria; Arrichiello, Antonio; Carrafiello, Gianpaolo; Nosotti, Mario; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of work: Lung microwave ablation (MWA) is considered an alternative treatment in high-risk patients, not suitable for surgery. The aim of our study is to compare MWA and pulmonary lobectomy in high-risk, lung cancer patients. Methods: This was a single-center, propensity score–weighted cohort study. All adult patients who underwent CT guided MWA for stage I NSCLC between June 2009-October 2014 were included in the study and were compared with a cohort of patients submitted to lung lobectomy in the same period of time. Outcomes were overall survival (OS) and disease-free survival (DFS). Results: 32 patients underwent MWA, and 35 high-risk patients submitted to lung lobectomy in the same period were selected. Median follow-up time was 51.1 months (95% CI: 43.8-62.3). Overall survival was 43.8 (95% CI: 26.1-55) and 55.8 months (95% CI: 49.9-76.8) in the MWA group and Lobectomy group, respectively. Negative prognostic factors were MWA procedure (HR:2.25, 95% CI: 1.20-4.21, p= 0.0109) and nodule diameter (HR: 1.04, 95% CI: 1.01-1.07; p= 0.007) for OS, while MWA procedure (HR: 5.2; 95% CI: 2.1-12.8: p < 0.001), ECOG 3 (HR: 5.0; 95% CI: 1.6-15.6; p = 0.006) and nodule diameter (HR: 1.1; 95% CI: 1.0-1.1; p = 0.003) for DFS. Conclusions: Our study demonstrated a high percentage of local relapse in the MWA group but a comparable overall survival. Although lung lobectomy remains the gold standard treatment for stage I NSCLC, we can consider the MWA procedure as valid alternative local treatment in high-risk patients for stage I NSCLC.